Bentuk Penyajian Tari Pisau Dua Pada Acara Bimbang Adat Di Desa Sendawar Bengkulu - Syinta Triagnesti; Herlinda Mansyur (FBS Universitas Negeri Padang, 2021)
This study aims to describe the Form of Presentation of Pisau Dua Dance At The Bimbang Adat (Wedding) Event in Sendawar Village, Semidang Alas Maras District, Seluma Regency, Bengkulu Province. Qualitative research type using a descriptive method of analysis. The data type uses primary data and secondary data. The main instrument used is the researcher himself and assisted with supporting instruments such as stationery, handy cam, and photo cameras. Data collection techniques are conducted by means of literature studies, observations, interviews, and documentation. The steps of analyzing data are collecting data, describing data, and concluding data. The results showed that the Pisau Dua Dance was performed at the Bimbang Adat (wedding) event in Sendawar Village, Semidang Alas Maras Subdistrict, Seluma Regency, Bengkulu Province is one of the traditional dances with a form of representational symbolic presentation and serves as entertainment. Pisau Dua dance consists of 6 varieties of motion, 2 dancers are all male, music (serunai and redap), makeup and costumes (no make-up) costumes (shirts, basic pants, peci/headgear, and half-masted fabric), property (2 pairs of knife two branches) and staging place (in front of pelaminan).